Peningkatan Daya Dukung Tiang pada Gedung Permata Indah Nganjuk Menggunakan Metode Trofimankove - Muchammad Sutikno; Edy Gardjito; Agata Iwan Candra; Fitry Rahmawaty; Muhammad Heri Nastotok (Kadiri University, 2021)
The function of the foundation as a substructure that transmits the load received from the upper structure of the building into the foundation makes the foundation have an important role. The strength of the foundation is something that needs to be planned properly. This planning aims to plan the foundation for the Permata Indah Building, Nganjuk Regency, which will later be used as a boarding house building. Planning that is carried out includes selecting the type of foundation, calculation of dimensions, and foundation reinforcement. Based on soil investigation results, the foundation type pile was chosen because the hard soil was located at a depth of 17 m. The method used to calculate the bearing capacity of the pile includes the Meyerhoff, Begemann, and Trofimankove methods. With a diameter of 30 cm and 4 poles, the carrying capacity of group piles (Pg) was obtained using the Meyerhoff method of 224.60 tons, the Begemann Method of 199.59, and the Trophimankove Method of 259.36 tons. From these results, the group pile bearing capacity value is still greater than the value of Æ©Vu= 146.28 tonnes. Meanwhile, for a single pile settlement Se= 2.13cm <Sijin= 3 cm SAFE and a pile settlement group Sg= 3.98cm.